Green, climate and sustainable finance: A bibliometric analysis - Becker, Michel; de Lima , Marcus Vinicius Andrade; Webber , Juliana Baldessar (Seven Editora, 2023)
Climate change has imposed challenges that have become a priority, and finance, which plays a key role in the economy, can adapt and incorporate devices to assist in this confrontation. In this environment, sustainable, climate and green finance compose emerging themes, with growing interest by researchers, not having consensus on their definitions, making it fundamental to understand and analyze the related scientific production. The article aimed to expand the understanding of these themes through a bibliometric study, pointing out authors, journals, keywords and relevant articles. The research highlighted authors J. Timmons Roberts and Farhad Taghizadeh-Hesary, as well as the journals Journal of Sustainable Finance, Investment; Climate Policy; and Sustainability, as the most prolific and presented a set of articles and keywords that may subsidize future work. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-127